KEARIFAN SOSIAL MASYARAKAT SASAK MELALUI TRADISI MELAMPAK DI KECAMATAN LINGSAR LOMBOK BARAT - Zaen udin Mansyur (Schemata: Jurnal Pasca Sarjana IAIN Mataram, 2019)
The melampak tradition is one of the unique traditions practiced by the Sasak people in Lingsar District, West Lombok. Its uniqueness is evidenced by the stages of its implementation outside of the habits of other people in the ceremony of death. It is a tradition that has taken root in society which is marked by the spirit of the community in preserving it. Social sanctions in the form of ridicule, dislike, and hostility are the result of people who do not practice it. The initial stage is carried out by providing ritual tools such as potpourri, kembang rampai, dulang/andang-andang, air wangi, lekesan, beras putek, kemek, kepeng tepong, kemenyan.. Furthermore, it is carried out with a roah accompanied by the supply of goods according to the needs of the deceased during his life and then brought to the kiyai house who has been taking care of the body as a stage of the closing process. Disappearance or melampak tradition in the event of this death has been running steadily in the community because it is driven by the community's concern that this tradition will be lost, the heritage of ancestors, and education of the value of mutual cooperation. Thus, this tradition can not be claimed to develop as activities that deviate from the values ??of sayari`ah even theologically it is still sourced from the laws of the Shari?ah al-Qur`an and al-Hadith. Then sociologically the practice activities of outbreak can encourage the spirit of community social practices such as mutual cooperation, silaturrahim, and help. While anthropologically, this tradition is the legacy of ancestors who continue to strengthen the family atmosphere in society.